ACG Clinical Guideline: Diagnosis and Management of Biliary Strictures. (17th March 2023) - Elmunzer, B. Joseph; Maranki, Jennifer L.; Gómez, Victoria; Tavakkoli, Anna; Sauer, Bryan G.; Limketkai, Berkeley N.; Brennan, Emily A.; Attridge, Elaine M.; Brigham, Tara J.; Wang, Andrew Y.
Abstract : A biliary stricture is an abnormal narrowing in the ductal drainage system of the liver that can result in clinically and physiologically relevant obstruction to the flow of bile. The most common and ominous etiology is malignancy, underscoring the importance of a high index of suspicion in the evaluation of this condition. The goals of care in patients with a biliary stricture are confirming or excluding malignancy (diagnosis) and reestablishing flow of bile to the duodenum (drainage); the approach to diagnosis and drainage varies according to anatomic location (extrahepatic vs perihilar). For extrahepatic strictures, endoscopic ultrasound-guided tissue acquisition is highly accurate and has become the diagnostic mainstay. In contrast, the diagnosis of perihilar strictures remains a challenge. Similarly, the drainage of extrahepatic strictures tends to be more straightforward and safer and less controversial than that of perihilar strictures. Recent evidence has provided some clarity in multiple important areas pertaining to biliary strictures, whereas several remaining controversies require additional research. The goal of this guideline is to provide practicing clinicians with the most evidence-based guidance on the approach to patients with extrahepatic and perihilar strictures, focusing on diagnosis and drainage.